Legislative immobility and judicial activism: the impact on the separation of powers in South Africa - Labuschagne, Pieter (Faculty of the Humanities, University of the Free State, 2013)
The division between the legislature/executive and the judiciary in a constitutional state is a very important, but precarious relationship. It is important that the political arm (legislature/executive) understand the critical role of the judiciary as custodian of the Constitution within the constitutional framework. Without the basic respect for and understanding of the role of the judiciary, politicians in the government can easily frustrate the judiciary primary function to uphold the law and to establish the rule of law in a country. If the relationship deteriorates and the status of the judiciary is degraded by the ruling party it will in the long run tarnish the status of the constitutional state and that of the rule of law in the country. This article deals with the internal process to initiate a private members bill in parliament with an explanation how easily it can be frustrated by the majority party in the standing committees and in parliament. The passing of the private members bill could be frustrated by the ruling party by using their numerical advantage. However, it is also pointed out that the purpose or goal of the same private members bill could also be reached by other means, such as a ruling by the High Courts. The article analyse this phenomenon and outlines the potential impact thereof on the principle of the separation of powers in South Africa.
Keywords: Constitutional state; Judiciary; Legislature; Executive; Supreme Court of Appeal